2021
DOI: 10.3390/su13020827
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-Temporal Changes of Land-Use/Land Cover Change and the Effects on Ecosystem Service Values in Derong County, China, from 1992–2018

Abstract: Monitoring the spatio-temporal variation of the land-use/land cover change (LULC) and ecosystem service value (ESV) changes will help achieve regional sustainable development and management. Derong County is a part of the Hengduan Mountains area, the most crucial ecological functional area in China, and LULC has changed tremendously in the past 30 years. However, the effects of LULC changes on ecosystem services is not well understood. Based on 1992, 1995, 2005, 2013, and 2018 remote sensing images, we used vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 51 publications
2
10
0
Order By: Relevance
“…The sensitivity analysis was done to test the reliability of our estimation of ESV, and it confirmed that our estimation of ESV is robust since the value of the coefficient of sensitivity (CS) is lower than 1 in all the cases, which is much similar to other studies by Tolessa et al [17], Gashaw et al [74], Hasan et al [18], and Wang et al [88]. However, we understand and believe that Costanza et al [3] developed the value coefficient for different land cover types for global estimation and might underestimate real services of land cover types in the local context.…”
Section: Assessment Of Urban Ecosystem Service Valuessupporting
confidence: 83%
“…The sensitivity analysis was done to test the reliability of our estimation of ESV, and it confirmed that our estimation of ESV is robust since the value of the coefficient of sensitivity (CS) is lower than 1 in all the cases, which is much similar to other studies by Tolessa et al [17], Gashaw et al [74], Hasan et al [18], and Wang et al [88]. However, we understand and believe that Costanza et al [3] developed the value coefficient for different land cover types for global estimation and might underestimate real services of land cover types in the local context.…”
Section: Assessment Of Urban Ecosystem Service Valuessupporting
confidence: 83%
“…This shows that the benefit transfer method has huge uncertainties in calculating ESV [74]. Some studies have conducted sensitivity-analysis based on elasticity-sensitivity coefficient to study the impact of changes in ES coefficients on ESV assessment [75,76]. However, Aschonitis et al [77] pointed out the elasticity-sensitivity coefficient should be used for ranking the importance of land use and land cover (LULC) changes rather than assessing the robustness and sensitivity of the ES coefficients.…”
Section: Uncertainties In Esv Assessmentmentioning
confidence: 99%
“…Human disruption of the ecosystem is becoming more common as the economy and urbanization develop. The question of conserving the environment while increasing its supply has become a global issue [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%